FHL1‐mutated reducing body myopathy. Issue 2 (5th December 2019) - Lim, Ka Young; Kim, Hyun Hee; Sung, Jung‐Joon; Oh, Byung‐Mo; Kim, Keewon; Park, Sung‐Hye
Abstract : Here, we report about reducing body myopathy, associated with a mutation in the four and a half LIM domain 1 gene ( FHL1 ), identified in a 40‐year‐old woman who was suffering from subtle muscle weakness since the age of six and a limping gait since the age of 22 years. In addition to her elevated muscle enzyme level and magnetic resonance imaging, myopathy was highly suspected considering progression of symptoms. Nerve conduction studies and electromyogram suggested myopathy. The muscle biopsy revealed severe dystrophic features with many reducing bodies on hematoxylin and eosin, nicotinomide adenine dinucleotide dehydrogenase‐tetrazolium reductase (NADH‐TR), and modified Gomori stains and ubiquitin immunohistochemistry. Whole‐exome sequencing revealed Xq26.3 encoding FHL1 missense mutations (NM_001159704) in exon 4: p.C150R, c.T448C. FHL1 ‐mutated "reducing body myopathy" is worth reporting based on its rarity and unique clinicopathologic features including ultrastructure. The confirmative diagnosis is still very difficult before gene analysis because clinical and pathological features of this disease overlap with other myofibrillar myopathies. We stress the importance of genotype‐phenotype correlation to obtain a precise diagnosis.